An interdomain network: the endobacterium of a mycorrhizal fungus promotes antioxidative responses in both fungal and plant hosts. Issue 1 (23rd February 2016) - Vannini, Candida; Carpentieri, Andrea; Salvioli, Alessandra; Novero, Mara; Marsoni, Milena; Testa, Lorenzo; de Pinto, Maria Concetta; Amoresano, Angela; Ortolani, Francesca; Bracale, Marcella; Bonfante, Paola
Summary: Arbuscular mycorrhizal fungi (AMF) are obligate plant biotrophs that may contain endobacteria in their cytoplasm. Genome sequencing of Candidatus Glomeribacter gigasporarum revealed a reduced genome and dependence on the fungal host. RNA‐seq analysis of the AMF Gigaspora margarita in the presence and absence of the endobacterium indicated that endobacteria have an important role in the fungal pre‐symbiotic phase by enhancing fungal bioenergetic capacity. To improve the understanding of fungal–endobacterial interactions, iTRAQ (isobaric tags for relative and absolute quantification) quantitative proteomics was used to identify differentially expressed proteins in G. margarita germinating spores with endobacteria (B+), without endobacteria in the cured line (B−) and after application of the synthetic strigolactone GR24. Proteomic, transcriptomic and biochemical data identified several fungal and bacterial proteins involved in interspecies interactions. Endobacteria influenced fungal growth, calcium signalling and metabolism. The greatest effects were on fungal primary metabolism and respiration, which was 50% higher in B+ than in B−. A shift towards pentose phosphate metabolism was detected in B−. Quantification of carbonylated proteins indicated that the B− line had higher oxidative stress levels, which were also observed in two host plants. This study shows that endobacteria generate a complex interdomain network that affects AMF and fungal–plant interactions.